2007
DOI: 10.1001/archneur.64.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of Autonomic Dysfunction May Predict Poor Prognosis in Patients With Multiple System Atrophy

Abstract: Background: Multiple system atrophy (MSA) is diverse in clinical phenotype, disease progression, and prognosis. Sudden death is a leading cause of death in patients with MSA. Objective: To determine what clinical factors affect the progression and survival prognosis of those with MSA. Design: A retrospective review of the medical records of 49 consecutive Japanese patients with pathologically confirmed MSA (29 men and 20 women; mean±SD age at onset, 59.8±6.5 years). Cox proportional hazards models were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 15 publications
7
109
2
1
Order By: Relevance
“…In our study, this association was confirmed by differences found in the survival analysis based on onset symptoms. Other studies have reported that patients with autonomic failure at disease onset had worse prognoses than those that exhibited cerebellar ataxia at onset [19,20]. In the current study, we found the same association even though the definition of autonomic failure in the national registry might be different from that in previous studies.…”
Section: Sakushima Et Al Page 10supporting
confidence: 59%
“…In our study, this association was confirmed by differences found in the survival analysis based on onset symptoms. Other studies have reported that patients with autonomic failure at disease onset had worse prognoses than those that exhibited cerebellar ataxia at onset [19,20]. In the current study, we found the same association even though the definition of autonomic failure in the national registry might be different from that in previous studies.…”
Section: Sakushima Et Al Page 10supporting
confidence: 59%
“…Nagaoka et al [10] speculated that long-term abnormalities of sympathetic nervous system attenuated the effect of leptin on lipolysis and induced disease-specific low energy expenditure, which is recognized as leptin Meanwhile, no significant differences in daily caloric intake were observed according to ADL level in patients with MSA-P. This can be explained by evidence indicating that swallowing disturbances are more frequently observed in patients with MSA-P than in those with MSA-C, and acted as a secondary cause of decreased daily caloric intake [11] . Smaller BMIs in MSA-P patients compared to MSA-C patients may also be explained by a difference in the frequency of dysphagia.…”
Section: Discussionmentioning
confidence: 96%
“…At present, frequent compensatory measures for dysphagia, such as the adjustment of diet type, liquid thickness, or swallowing posture, are more realistic strategies for maintaining the quality of life of patients with MSA-P as well as those with Parkinson's disease [19]. However, dysphagia in patients with early stage MSA-C has been predicted to be less remarkable than in patients with MSA-P [20]. Therefore, we should first adjust the diet type for patients with early stage MSA-C to allow them to form a food bolus smoothly in the oral phase, but, in the late stage, patients with both MSA-P and MSA-C will need an ultimate alternative, such as tube feeding, in preventing aspiration pneumonia and considering the optimal timing for a gastrostomy [13].…”
Section: Figurementioning
confidence: 99%